Penggunaan Suplemen Makanan Pada Balita Untuk Memenuhi Kebutuhan Mikronutrien - Luluk Yuliati; Munisah Munisah (Universitas Muhammadiyah Gresik, 2022)
Supplement consumption was the activity using or consumption supplement to meet the requirement of malnutrition in daily food. The factor can be influence by family, health condition, intake of nutrient, mass media, and as well as knowledge of supplement. The research purpose was to know the relationship between the knowledge of mother about supplement and the consumption in toddlers. The research use correlation descriptive with cross sectional approach. The sample were the mother of childhood in kindergarten of Istiqomah Ungaran, Using by total sampling and that accounted 84 respondent, and the data was collected by questionnaire. The result of univariate research showed that 64,3% respondent have a good knowledge and 63% was consumption supplement well. The result of bivariate analysis with chi square test was showed that any significant relationship between the knowledge of mother about supplement with supplement consumption of child in 4-5 year’s old with p value 0,037 (p<α). Finally, for the next study is to know factor which affected the supplement consumption of childhood. And the health provider should improve their abilities to give communication, information and education about food supplement for childhood that use for increasing the mother knowledge about supplement consumption of childhood.